Economic feasibility of growing medicinal crops under irrigation through water-harvesting tank with gabions in Vertisol of Malwa region - RANADE, D H; JAIN, L K; VISHWAKARMA, S K; TOMAR, A S (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 2000-2001 to assess the economic viability of a water-harvesting tank for irrigating the winter crops. The run-off water collected in a water-harvesting tank, constructed using gabion structures, was utilized for irrigating the winter crops during the scanty rainfall year in Indore district of Malwa region. Based on the expenditure incurred and yield data, the economic evaluation of the irrigation system was worked out. Constructing tank and recycling water for irrigation was found econdmically viable (benefit: cost ratio 1.53: 1) and very effective in improvingthe crop productivity of ashwagandha (Withania somnifel'a Daunal) from 0 (without irrigation) to 220 kg/ha Grain yield.The availability of sufficient water thus provided multiple options to adopt more remunerative cropping system of medicinal crops that need assured irrigation other than the traditional crops.